THE ROLE OF PHONETICS IN SECOND LANGUAGE ACQUISTION (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: Phonetics plays a crucial role in second language acquisition (SLA) and affects students' pronunciation, listening comprehension and overall communicative competence. This paper explores the importance of phonetic awareness in SLA by examining how phonetic features of target and native languages ​​affect language learning. He emphasizes the importance of teaching phonetic elements such as segmental and segmental suprasegmental features to improve students' ability to correctly perceive and produce sounds. In addition, he discusses the implications of phonetic training for teachers and students, emphasizing the need for pedagogical approaches that integrate phonetics in language teaching.